Available methods to enhance regenerative potential of plastic materials for bone defects replacement in orthopedics. Part 1. Autologous platelet rich plasma - A. M. Fayn; A. Yu. Vaza; S. F. Gnetetskiy; K. I. Skuratovskaya; V. B. Bondarev; Yu. A. Bogolyubskiy; R. S. Titov; A. Yu. Sergeev (Трансплантология (Москва))
The main method of surgical treatment of patients with post-traumatic disorders of bone regeneration is the use of bone grafting. Until now, the optimal plastic material has been a bone autograft, which use involves additional trauma to the patient. Alternative materials that are used for grafting have only an osteoconductive effect, of varying effectiveness. To optimize the properties of plastic materials, giving them an osteostimulating effect, they can be used in combination with biologically active substances. A source of biologically active substances can be platelet-rich plasma, platelet lysate and red bone marrow. This literature review includes a description of three main methods to stimulate osteogenesis. The first part examines the mechanism of action of platelet-rich plasma, indications and contraindications for its use, describes the results of treatment when platelet-rich plasma is used to stimulate osteogenesis. Platelet-rich plasma is a product of a human native blood obtained by centrifugation. The output is a high concentration of platelets in a small volume of plasma, which contain growth factors and cytokines that have a direct effect on the regeneration process. Local platelet-rich plasma therapy is performed to stimulate osteogenesis. Autologous platelet-rich plasma with growth factors contained in α-granules of platelets is injected into an allogeneic graft or into a fracture zone. The aim of this article is to summarize the results of treatment using platelet-rich plasma to improve bone regenerative potential in orthopaedics.